2005
DOI: 10.1007/s10741-005-7539-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Suspected Diastolic Dysfunction in Patients with a Clinical Diagnosis of Congestive Heart Failure

Abstract: Normal LV systolic function was seen in nearly one-half of the echocardiograms with a suspected clinical diagnosis of CHF. Suspected LV diastolic dysfunction was observed in one-third of the echocardiograms with a suspected clinical diagnosis of CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…It is possible that an increased BMI was a factor for the perceptions of breathlessness in our DHF patients, but the matched control group had similar BMI and no symptoms. We found that DHF patients were older and more likely to be female than SHF patients (a frequently reported observation in heart failure epidemiology reports) 13. Previous studies have shown that female CHF patients perceive dyspnoea differently from males 29.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…It is possible that an increased BMI was a factor for the perceptions of breathlessness in our DHF patients, but the matched control group had similar BMI and no symptoms. We found that DHF patients were older and more likely to be female than SHF patients (a frequently reported observation in heart failure epidemiology reports) 13. Previous studies have shown that female CHF patients perceive dyspnoea differently from males 29.…”
Section: Discussionsupporting
confidence: 49%
“…Epidemiological studies suggest that heart failure with normal ejection fraction (HeFNEF), often labelled “diastolic heart failure” (DHF) is common, and has a prognosis similar to that of systolic heart failure (SHF) 13. On the face of it, this observation sits oddly with the observation in large trials that increasing left ventricular ejection fraction (LVEF) is strongly predictive of better outcome in heart failure populations 46.…”
mentioning
confidence: 99%